The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1365-2672.2007.03563.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the microbial community in biological processes treating industrial and domestic wastewaters

Abstract: Aims:  Comparison of the microbial composition and process performance between laboratory scale processes treating domestic and vegetable oil wastewaters. Methods and Results:  Two laboratory scale modified Ludzack–Ettinger processes were operated under similar operating conditions. One process was fed domestic wastewater and the other an industrial wastewater, vegetable oil effluent. Nitrogen removal capacities of the processes were similar. The industrial process exhibited a lower COD removal capacity and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous studies on activated sludge communities mainly focused on lab-scale bioreactors. Only a few studies have analyzed the microbial diversity of activated sludge communities in full-scale WWTPs. It was reported that the microbiology is more complex in full-scale WWTPs than in lab-scale bioreactors. , Consequently, the study of the microbial community composition and dynamics in full-scale WWTPs is of great importance to obtain practically useful information for improvement of wastewater treatment performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on activated sludge communities mainly focused on lab-scale bioreactors. Only a few studies have analyzed the microbial diversity of activated sludge communities in full-scale WWTPs. It was reported that the microbiology is more complex in full-scale WWTPs than in lab-scale bioreactors. , Consequently, the study of the microbial community composition and dynamics in full-scale WWTPs is of great importance to obtain practically useful information for improvement of wastewater treatment performance.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on activated sludge communities have focused on monitoring the spatial and temporal changes in microbial diversity, , investigating microbial community structure, ,, demonstrating the correlation of microbial diversity with bioreactor operating parameters, , linking biodiversity to bioreactor stability, , and assessing the impact of certain toxins on microbial diversity …”
Section: Introductionmentioning
confidence: 99%
“…EUBmix counts in sample from WWTP Degenaar et al [20] showed similar community structure profile during domestic wastewater treatment process. The numerically dominant group was Betaproteobacteria (33%), followed by Alphaproteobacteria at 26% and Gammaproteobacteria at 15%.…”
Section: Fig 2 Percentages Of Group-specific Probes Relative Tomentioning
confidence: 91%
“…Consequently, the study of the microbial community composition and dynamics in full-scale WWTPs is of great importance to obtain practically useful information for improvement of wastewater treatment performance. Moreover, although phylogenetic analyses targeting 16S rRNA gene have been performed widely, few studies have examined the link between the results of such analyses and wastewater treatment functions of activated sludge other than specific functions related to nitrogen and phosphorus removal (Gilbride et al 2006;Degenaar et al 2008). Gilbride et al (2006) monitored the microbial community composition in a WWTP of a bleached kraft pulp mill using denaturing gradient gel electrophoresis and terminal-restriction fragment length polymorphism (T-RFLP) analyses, and found significant correlations between several taxa and performance indicators such as chemical oxygen demand removal and the sludge volume index.…”
Section: Introductionmentioning
confidence: 99%